IMPLEMENTASI FILTER SKETSA CITRA DIGITAL MELALUI OPERASI KONVOLUSI DENGAN MATRIK KERNEL LAPLACE OF GAUSS - Bunbun Muhammad; Tedjo Darmanto; Ryan Gustira Haryanto Putra (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Sketch filter is used usually as a preliminary process of the images due to further processing such as in pattern recognition of a certain object by deep learning method. Several types of sketch filter can be used to detect the edge of object. In this paper the implementation of convolution operation by the Laplace of Gauss kernel matrix is explored to be used as a sketch filter to detect the edge of object.